Imaginary nation at the juncture of the Movement of Tupac Amaru II. Eighteenth century and projections in the XXI century - Ríos Burga, Jaime (2017)
The essay reconstructs aspects of the imaginary of nation at the juncture of the Movement of Tupac Amaru II as part of nation building in the modern world of the eighteenth century colonial system. We start from a global historical location, and then focus on their relationship with the imaginary of the nation state and nation state present in Western civilization. To eventually rebuild their specificities in the tupacamarista American anticolonial movement. Socio-political and discursive processes as a creative / productive function internalized in consciousness / collective unconscious of specific national movements defining not only the psyche and society as ideologies but changes and continuities in their collective minds in a historical long time.